Analysis of the MTSN 2 Poso Education Data Collection System Using the Cognitive Walkthrough Method - Rizaldi Agil Faturrahman; Amriana Amriana; Deny Wiria Nugraha; Rizka Ardiansyah; Dessy Santi (Eduvest - Journal of Universal Studies, 2026)
This study examines the usability of the EMIS 4.0 website at MTsN 2 Poso using the Cognitive Walkthrough method. The increasing implementation of digital education management systems requires educational institutions to ensure that information systems are efficient, user-friendly, and capable of supporting accurate educational data management. However, several users of EMIS 4.0 still experience difficulties operating the system, particularly when completing administrative tasks. Therefore, this research aims to evaluate the usability level of EMIS 4.0 by identifying task completion success, user errors, efficiency, and user experience during system interaction. This study employed a quantitative usability evaluation approach using the Cognitive Walkthrough method. Data were collected from 20 teachers and education personnel selected through purposive sampling. Respondents were asked to complete seven task scenarios related to the use of EMIS 4.0. The results showed that the task completion rate reached 85%, while the error rate was 26%. Several tasks, such as updating employment data, uploading attendance documents, and printing portfolios, required longer completion times than other tasks. The time-based efficiency score obtained was 0.0272 goals/second. The findings indicate that EMIS 4.0 still requires improvements in interface design, feature accessibility, and server performance. In conclusion, the Cognitive Walkthrough method effectively identified usability problems and provided recommendations for improving the usability and user experience of the EMIS 4.0 system.